Sur les traces d’un « sujet en devenir » - Daniel Favre (Éducation et Socialisation)
Depending on the scientific disciplines, there are multiple ways, explicit or implicit, to picture a subject. The autonomy of a subject, or of a machine, increases if this one can have feedbacks which inform him about the result of his actions. The human being with his frontal lobes is biologically equipped to be aware of the feedbacks coming from the sensory organs, the muscles and the joints of his body. He will thus be able to carry out an action program and to check its execution. Self-regulation, and thus the capacity for a subject to become a little more a subject, could depend on an education allowing one to become more conscious of the coupling between the activity of feeling and the activity to think, which we call: “to think what one feels and to feel what one thinks”. This method showed its effectiveness within the framework of the prevention of violence and school failure.